2023
DOI: 10.1002/idm2.12090
|View full text |Cite
|
Sign up to set email alerts
|

Halide‐based solid electrolytes: The history, progress, and challenges

Abstract: Lithium metal solid‐state batteries (LMSBs) have attracted extensive attention over the past decades, due to their fascinating advantages of safety and potential for high energy density. Solid‐state electrolytes (SEs) with fast ionic transport and excellent stability are indispensable components in LMSBs. Heretofore, a series of inorganic SEs have been extensively explored, such as sulfide‐ and oxide‐based electrolytes. Unfortunately, they both have difficulty in achieving a satisfactory balance of conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 126 publications
0
7
0
Order By: Relevance
“…The superionic halides have recently received much attention because they show high electrochemical stability towards high-potential cathode active materials, and they can be synthesized via solution-based approaches. [21,[27][28][29][30][31][32] Additionally, the degree of decomposition for halides was reported as much lower than for the sulfides cell with conductive additives, making halide-based systems even more attractive for an indepth investigation to mitigate the problem mentioned above. [18,[22][23][24][25][26] Since the majority of the exploited polymer binders used in the halide-based systems necessitated the use of organic solvents, the interest in the development of the processes with the use of other 'greener' solvents is high.…”
Section: Introductionmentioning
confidence: 99%
“…The superionic halides have recently received much attention because they show high electrochemical stability towards high-potential cathode active materials, and they can be synthesized via solution-based approaches. [21,[27][28][29][30][31][32] Additionally, the degree of decomposition for halides was reported as much lower than for the sulfides cell with conductive additives, making halide-based systems even more attractive for an indepth investigation to mitigate the problem mentioned above. [18,[22][23][24][25][26] Since the majority of the exploited polymer binders used in the halide-based systems necessitated the use of organic solvents, the interest in the development of the processes with the use of other 'greener' solvents is high.…”
Section: Introductionmentioning
confidence: 99%
“…The use of flammable organic electrolytes poses an increasing safety concern on conventional Li-ion batteries, especially for large-scale applications such as electric vehicles and energy storage systems. [1,2] Replacing flammable liquid electrolytes with nonflammable inorganic solid-state electrolytes (ISSEs) has been regarded as the most promising way to radically improve the battery safety for future development. [3][4][5][6][7] However, it is noticed that the solid electrolyte layer in current solid cells is usually over 500 μm in thickness, in some cases even to 1 mm, 30-60 times that of conventional polyolefin separators (≈15 μm) in commercial lithium-ion batteries (LIBs).…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37] Compared with oxide SSEs, halide SSEs do not require high-temperature sintering and exhibit better mechanical flexibility, which can be cold-pressed. [2,38] In addition, halide SSEs are relatively light (e.g., 2.69 g cm −3 for Li 3 InCl 6 vs 5.11 g cm −3 for Li 7 La 3 Zr 2 O 12 ), which makes them a promising candidate for practical all-solid-state Li batteries (Figure 1b). [39,40] Compared with sulfide SSEs, halide SSEs are environmentally friendly (no toxic gases are produced when exposed to air).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, halide SEs have emerged as promising alternatives due to their wide ESW, deformability, and high ionic conductivity similar to that of sulfide SEs. However, the current research on halide SEs mainly focuses on lithium halides for LMBs (e.g., Li 3 MX 6 ; M = In, Y, and Sc; X = F, Cl, and Br). The studies conducted on sodium halides for SMBs are still limited. , It has been reported that the ionic conductivities of NaAlCl 4 and NaZrCl 4 are 3.9 × 10 –6 and 1.8 × 10 –5 S/cm at 30 °C, respectively.…”
mentioning
confidence: 99%